Sengketa Merek Strong dan Penggunaan Kata Umum pada Merek Dagang (Studi Putusan Mahkamah Agung 332 K/ Pdt.Sus-Hki/2021) - Sihombing, Silvia; Aminah (UNES Law Review, 2023)
Trademark becomes a valuable asset owned by a company, especially if the brand has become a well-known mark. The well-known of a trademark creates a greater opportunity for deviations in the use of the brand which will eventually lead to the trademark disputes. Trademark disputes are still common in Indonesia with various problems, especially imitation of famous trademarks. The purpose of this study was to determine the decision process of the judiciary regarding the "STRONG" trademark dispute from the first level and an appeal and to see its conformity with the applicable laws and regulations and justice for the disputing parties.The approach method used in this thesis is normative juridical, namely research that uses existing legal norms and the application of these legal norms with research specifications is descriptive-analytical. The results showed that the Supreme Court in Decision Number 332 K/Pdt.Sus-HKI/2021 which stated that the considerations at the Central Jakarta Commercial Court were wrong in applying the law, had given correct considerations and decisions in accordance with applicable laws and regulations. The Defendant/Applicant for Cassation has not violated the rights to the “STRONG” trademark belonging to the Plaintiff/Respondent of Cassation. In order to be able to use a trademark in the form of a general descriptive word, it must build a secondary meaning on the trademark so that it can become a stand-alone trademark and has a strong distinguishing power. The need for additional criteria and use of trademark in the form of descriptive general words in the laws and regulations concerning trademarks in Indonesia.